An Econometric Technique for Comparing Median Voter and Oligarchy Choice Models of Collective Action: The Case of the Nato Alliance - Murdoch, James C.; Sandler, Todd; Hansen, Laurna (The Review of Economics and Statistics, 1991)
This paper devises an empirical methodology for discriminating between the median voter model and the oligarchy choice model when applied to the collective provision of a public good. In particular, an empirical methodology is engineered so that a nested test procedure can evaluate competing models. The authors apply this methodology to examine the demand for military activities of ten members of the NATO alliance. A two-stage least squares procedure, corrected for autocorrelation, is used to estimate the demand equations. Test results vary: some allies abide by the median voter model, others by the oligarchy model, and still others by neither. Copyright 1991 by MIT Press.